2010
DOI: 10.1111/j.1532-5415.2010.03169.x
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Weight Loss and Incident Dementia in an Elderly African-American Cohort

Abstract: OBJECTIVES-To examine the association between changes in body mass index (BMI), dementia, and mild cognitive impairment (MCI). DESIGN-Prospective observational study.SETTING-Urban community in Indianapolis, Indiana. PARTICIPANTS-Participantswere African Americans aged 65 and older enrolled in the Indianapolis Dementia Project and followed through 2007. This analysis included 1,331 participants who did not have dementia at their first BMI measurement. MEASUREMENTS-Cognitive assessment and clinical evaluations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 27 publications
8
77
2
1
Order By: Relevance
“…Our result regarding weight loss being associated with increased dementia related mortality risk fits with studies using clinical dementia as end point (10)(11)(12)(13)(14)(15)(16)(17)(18). Most previous studies investigate weight change in old age, typically above 65 years or older, where reverse causality might be a plausible explanation for the association between weight loss and dementia.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our result regarding weight loss being associated with increased dementia related mortality risk fits with studies using clinical dementia as end point (10)(11)(12)(13)(14)(15)(16)(17)(18). Most previous studies investigate weight change in old age, typically above 65 years or older, where reverse causality might be a plausible explanation for the association between weight loss and dementia.…”
Section: Discussionsupporting
confidence: 74%
“…A better understanding of the association between body weight and dementia may be achieved by studying weight trajectories and patterns from midlife into old age (1). Studies with weight at multiple time points have generally reported weight loss (10)(11)(12)(13)(14)(15)(16)(17)(18) or weight instability (19) to be associated with increased dementia risk. However, many of these studies are limited to weight trajectories in old age, and might be prone to reverse causality because dementia and preclinical dementia might cause weight loss (1,20).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, we found no evidence of change in BMI or weight over 2 years in biomarker "positive" vs "negative" groups although multiple studies have demonstrated that weight loss is a nonspecific preclinical marker of AD that may be present 6 -10 years prior to the onset of clinically recognizable cognitive and functional symptoms. 11,26 Both autopsy and imaging data suggest that weight loss may in part be related to brain pathology. An autopsy study of individuals with and without dementia found that AD plaque and tangle pathology was associated with both low BMI and declining BMI in the years preceding death.…”
Section: Resultsmentioning
confidence: 99%
“…경도인지장애 환자 중 10~15% 는 매년 알츠하이머 병으로 진단되고, 6년 후에는 80%가 치매로 진행된다 [6]. 노인의 인지수준에 영향을 미치는 신체적 증상에는 현재 체질량 지수 [7,8]와 최근 체질량 지수의 감소 [7], 최 근 체중감소 [9] …”
unclassified